The evolution of magnetic resonance enterography in the assessment of motility disorders in children. Issue 107 (October 2018) - Menys, A.; Saliakellis, E.; Borrelli, O.; Thapar, N.; Taylor, S.A.; Watson, T.
Highlights: Gastrointestinal symptoms represent common clinical problems for paediatric populations. In adults, MRI to evaluate gastric physiology and motility is increasingly popular as a research tool. MRI is non-invasive, safe and increasingly available making it a promising modality to inform our understanding of paediatric GI symptoms. Abstract: Gastrointestinal symptoms including constipation, diarrhoea, pain and bloating represent some of the most common clinical problems for patients. These symptoms can often be managed with cheap, widely available medication or will spontaneously resolve. However, for many patients, chronic GI symptoms persist and frequently come to dominate their lives. At one end of the spectrum there is Inflammatory Bowel Disease (IBD) with a clearly defined but expensive treatment pathway. Contrasting with this is Irritable Bowel Syndrome (IBS), likely a collection of pathologies, has a poorly standardised pathway with unsatisfactory clinical outcomes. Managing GI symptoms in adult populations is a challenge. The clinical burden of gastrointestinal disease is also prevalent in paediatric populations and perhaps even harder to treat. In this review we explore some of the recent advances in magnetic resonance imaging (MRI) to study the gastrointestinal tract. Complex in both its anatomical structure and its physiology we are likely missing key physiological markers of disease through relying on symptomatic descriptors of gut function. Using MRI we might be able to characterise previously opaque processes, such as non-propulsive contractility, that could lead to changes in how we understand even common symptoms like constipation. This review explores recent advances in the field in adult populations and examines how this safe, objective and increasingly available modality might be applied to paediatric populations.